Senegal Economic Update, December 2014 : Learning from the Past for a Better Future - World Bank Group (Washington, DC, 2015)
Gross domestic product (GDP) growth was a disappointing 3.5 percent in 2013. It remained largely unchanged compared to 2012, reflecting a decline in cereal production and stagnation in the industrial sector. Services continue to drive the economy. The economic outlook for 2014 was more positive, but poor rainfall and the Ebola outbreak have forced downward revisions in GDP growth projections, now expected to reach 4.5 percent. The plan Senegal emergent aims to break with this trend, with a welcome focus on higher economic growth. However, its ambitions may exceed available resources and will likely depend on accelerated reforms and a strong private sector response. This first economic update begins with an overview of the macroeconomic situation in Senegal, starting with a review of 2013 before examining the initial results of 2014. After a brief look at the challenges posed by unemployment and poverty, the report turns to an assessment of the growth strategy. It presents analysis of past performance since 1990 in order to understand better what needs to be done differently. The report concludes with a few recommendations.